Emissão de fluorescência e produção de massa seca em feijão e soja em função da aplicação de nitrogênio em cobertura - MAFEI, Maloní Montanini (2009)
Nitrogen is considered an essential element for plants, since it is involved in the composition of various biomolecules such as ATP, NADH, NADPH, proteins, enzymes and chlorophyll. The chlorophyll is a pigment from the leaves of plants, which is directly associated with the potential of photosynthetic activity, as well as the nutritional status of the plant. The use of the variable fluorescence of chlorophyll has been widespread, especially in the study of photosynthetic capacity of plants, as a nondestructive method that allows qualitative and quantitative analysis of the absorption and utilization of light energy by photosynthetic apparatus. The objective of this research was to quantify the emission of the chlorophyll a fluorescence (F0, initial fluorescence; Variable-Fv, Fm-Maximum, Terminal-Ft and Efficiency Fotoquímica- Fv/Fm) in photosystem II and the dry matter in bean (Phaseolus vulgaris L .) and soybean (Glycine max (L.) Merr.) submitted the application of nitrogen in the form of ammonium sulfate in coverage. The experimental design was completely randomized in factorial formed by two legumes, two readings and two levels of nitrogen N0 = 0.000 g.kg-1 (control) and N1 = 0,060 g.kg-1. Nitrogen fertilization with ammonium sulfate in coverage influenced the minimum fluorescence (F0) and not influenced by other variables of fluorescence in bean and soybean. Increased the dry mass of branches for the bean, to have influenced the increase in soybean dry masses of shells of pods and number of pods